The Discourse of Islamic Religious Education in Strengthening Students' Moderate Attitudes - Alda Alda; Avrilia Puja; Syarina Syarina; Munawar Munawar; Muhammad Tang; Juhasdi Susono (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
The discourse of Islamic Religious Education (PAI) plays a strategic role in strengthening the moderate attitudes of students amidst the dynamics of social and religious diversity. This article aims to conceptually examine the role of Islamic Religious Education (PAI) discourse in shaping students' moderate attitudes thru an academic approach. This research uses the library research method by analyzing various sources of literature in the form of books, scientific journal articles, and educational policy documents relevant to the theme of PAI discourse and religious moderation. Data analysis is conducted descriptively-analytically to identify concepts, thot patterns, and main findings from the reviewed literature. The study results show that the dialogical, inclusive, and critical discourse of PAI can encourage students to understand differences rationally and instill values of religious moderation, such as tolerance, justice, and balance. Furthermore, academic discourse in Islamic Religious Education (PAI) provides a reflective space for students to understand Islamic teachings contextually without neglecting normative values. Thus, strengthening the discourse of Islamic Religious Education becomes a relevant approach in fostering moderate attitudes among students in the educational environment.